Students' Difficulties in Learning English - Yuliza Mahrian; Indah Ayu Br. Tarigan; Emya Gresta Br Sembiring; Ifdihansyah Lubis; Sheila Novita; Novita Purnama Sari Br. Hotang; Noor Muhammad Salim Sinaga (Indonesian Journal of ELT and Applied Linguistics, 2022)
In English learners, especially high school students, generally find it difficult in translation and vocabulary. This study aims to find out what difficulties students face in learning English. To achieve the research objectives, a qualitative research method was used with a case study design. The instrument of this research is observation where we observe students' participation in learning English. Then we also use other instruments such as interviews. The object of this research is students of class VII-4 SMP Negeri 1 Delitua. The number of students in this study were 15 students. Researchers found that many students find learning English difficult. From the results of interviews the highest difficulty faced by many students was in translating sentences, the second was lack of vocabulary, and the third was motivation. The researcher also found other factors that cause students' difficulties in learning English, namely there are students who like English and there are also those who do not like English.